2004
DOI: 10.1093/hmg/ddh201
|View full text |Cite
|
Sign up to set email alerts
|

Affected sib-pair analysis of the contribution of HLA class I and class II loci to development of cervical cancer

Abstract: Cervical cancer is a multifactorial disease and infection by oncogenic human papilloma viruses represents the main environmental risk factor. Only a subset of infections becomes persistent and develops into cancer, implying that genetic susceptibility factors are needed for malignant progression. Here, we use a population-based cohort of affected sib-pairs (ASPs) to examine the role of the human leukocyte antigen (HLA) class I and class II loci in cervical cancer susceptibility. Analysis of 278 ASPs revealed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 51 publications
0
25
1
Order By: Relevance
“…12,29 Several studies have shown some evidence supporting that certain HLA class II alleles or allele combinations could explain higher susceptibility in women with CC. 19,25,30,31 Our findings support previous studies that found the HLA-DR15/DQ*0602 haplotype to be positively associated with cervical neoplasia, 7,25,32 but this is inconsistent with other reports that have suggested a negative association. 33 Haplotypes HLA-B7/DQ*0302, 34 DR11/ DQ*0301, 29 DR4/DQ*0301, and DR1/DQ*0301 30 have been associated with CC susceptibility in Latin-American, Senegalese, and white American women.…”
Section: Discussioncontrasting
confidence: 77%
“…12,29 Several studies have shown some evidence supporting that certain HLA class II alleles or allele combinations could explain higher susceptibility in women with CC. 19,25,30,31 Our findings support previous studies that found the HLA-DR15/DQ*0602 haplotype to be positively associated with cervical neoplasia, 7,25,32 but this is inconsistent with other reports that have suggested a negative association. 33 Haplotypes HLA-B7/DQ*0302, 34 DR11/ DQ*0301, 29 DR4/DQ*0301, and DR1/DQ*0301 30 have been associated with CC susceptibility in Latin-American, Senegalese, and white American women.…”
Section: Discussioncontrasting
confidence: 77%
“…Cohort 1 was based on a nested study within the Northern Sweden Health and Disease Study Cohort [9]. Cohort 2 included women from families with at least two affected women from all of Sweden [17]. Two of the SNPs studied (rs2290907 and rs16970849) were found to be significantly correlated with cervical cancer (CIN3 and ICC) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Scandinavian countries, with well-established population registries, provide evidence for familial aggregation in cervical cancer incidence (and that of its immediate precursor, CIN3) (711). Those studies reported that cervical cancer risk associations are strongest for full-relatives, intermediate for half-siblings, and lowest for non-biological relatives.…”
Section: Introductionmentioning
confidence: 99%